Metabolites of 2,2'-dichlorobiphenyl and 2,6-dichlorobiphenyl in hairy root culture of black nightshade Solanum nigrum SNC-9O - Rezek, Jan; Macek, Tomas; Doubsky, Jan; Mackova, Martina (Chemosphere, 2012)
The hairy root culture of black nightshade (Solanum nigrum) SNC-9O was exposed to 2,2'-dichlorobiphenyl (PCB 4) and 2,6-dichlorobiphenyl (PCB 10) to follow the metabolites produced. The analytical standards of 4-hydroxy-2,2'-dichlorobiphenyl, 5'-hydroxy-2,2'-dichlorobiphenyl, 4-hydroxy-2,6-dichlorobiphenyl, 2-hydroxy-2',6'-dichlorobiphenyl, 3-hydroxy-2',6'-dichlorobiphenyl and 4-hydroxy-2',6'-dichlorobiphenyl have been synthesized. Hydroxy-metabolites of both PCB 4 and PCB 10 were present in the biomass. These appeared mainly as conjugates rather than as free hydroxy-PCBs, both maintained in plant cells. The concentrations of non-conjugated hydroxy-PCBs ranged between 0.9 and 35.2 μg kg(-1) of biomass fresh weight and the concentration of the conjugated ones ranged between 2.0 and 113.0 μg kg(-1) depending on the position of hydroxyl. The para- position of biphenyl (4 or 4') seems to be preferred for hydroxylation. Methoxy-PCBs and hydroxy-methoxy-PCBs have also been identified in plant cells. Hydroxyl in the meta-position (3, 3', 5 or 5') appears to be preferred for methylation in hydroxy-PCBs. Hydroxy-methoxy-PCBs have occurred in the conjugated form as well.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; polychlorované bifenyly; Chromatography, Gas; Hydroxylation; látky znečišťující životní prostředí; hydroxylace; Plant Roots; Polychlorinated Biphenyls; kořeny rostlin; Environmental Pollutants; Solanum nigrum; chromatografie plynová